Diagnosing HIV infection in patients presenting with glandular fever‐like illness in primary care: are we missing primary HIV infection?. Issue 1 (11th May 2012) - Hsu, DTS; Ruf, M; O'Shea, S; Costelloe, S; Peck, J; Tong, CYW
Abstract : Objectives: The aim of the study was to examine the prevalence of HIV infection in patients presenting in primary care with glandular fever (GF)‐like illness. Methods: Samples from primary care submitted for a GF screen between April 2009 and June 2010 were identified. Samples without an HIV request were anonymized and retrospectively tested using a 4th‐generation HIV antigen/antibody screening test. Reactive samples were further confirmed by an HIV antibody only test, with or without a p24 antigen assay. Antibody avidity testing based on the Recent HIV Infection Testing Algorithm (RITA) was used to identify individuals with evidence of recent acquisition (within 4–5 months). Results: Of 1046 GF screening requests, concomitant HIV requests were made in 119 patients. Excluding one known positive patient, 2.5% (three of 118) tested HIV positive. Forty‐five (4.3%) had a subsequent HIV test through another consultation within 1 year; of these, 4.4% (two of 45) tested positive. Of the remaining 882 patients, 694 (78.7%) had samples available for unlinked anonymous HIV testing, of which six (0.9%) tested positive. The overall HIV prevalence was 1.3% (11 of 857), with 72.7% (eight of 11) of cases missed at initial primary care presentation. Four of the nine (44.4%) available positive samples had evidence of recent acquisition, with three (75.0%) missed at initial primary care presentation. Conclusion: Low levels of HIV testing in patients presenting in primary care with GF‐like illness are resulting in a significant number of missed HIV and seroconversion diagnoses. Local policy should consider adopting an opt‐out strategy to include HIV testing routinely within the GF‐screening investigation panel.